2015
DOI: 10.1002/bit.25845
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids contribute to acetic acid resistance in Zygosaccharomyces bailii

Abstract: Lignocellulosic raw material plays a crucial role in the development of sustainable processes for the production of fuels and chemicals. Weak acids such as acetic acid and formic acid are troublesome inhibitors restricting efficient microbial conversion of the biomass to desired products. To improve our understanding of weak acid inhibition and to identify engineering strategies to reduce acetic acid toxicity, the highly acetic‐acid‐tolerant yeast Zygosaccharomyces bailii was studied. The impact of acetic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 54 publications
4
68
0
Order By: Relevance
“…It was found that exponentially-growing yeast cells adapted to a concentration of acetic acid that reduced their doubling time by 50% exhibited an increase in their total content of complex sphingolipids and extensive changes in the profile of the complex sphingolipids present, compared to cells cultivated in the same way, but not exposed to acetic acid [46]. The conclusions of our study are also in agreement with a recent report [52] providing evidence that the intrinsically high sphingolipid content in the PM of Zygosaccharomyces bailii , a hemiascomycete distantly related to S. cerevisiae , is an important contributor to the high acetic acid tolerance of this organism. In this regard, we demonstrated that, at least in S. cerevisiae , it is IPC and MIPC, and not M(IP) 2 C, that are required for acetic acid tolerance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that exponentially-growing yeast cells adapted to a concentration of acetic acid that reduced their doubling time by 50% exhibited an increase in their total content of complex sphingolipids and extensive changes in the profile of the complex sphingolipids present, compared to cells cultivated in the same way, but not exposed to acetic acid [46]. The conclusions of our study are also in agreement with a recent report [52] providing evidence that the intrinsically high sphingolipid content in the PM of Zygosaccharomyces bailii , a hemiascomycete distantly related to S. cerevisiae , is an important contributor to the high acetic acid tolerance of this organism. In this regard, we demonstrated that, at least in S. cerevisiae , it is IPC and MIPC, and not M(IP) 2 C, that are required for acetic acid tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…In this same regard, a scs7Δ mutant, which lacks an enzyme necessary to alpha-hydroxylate the VLCFA in sphingolipids, contains an altered spectrum of IPC species and is more sensitive to acetic acid than the corresponding parental strain [20]. Given that TORC2, Ypk1 and the mechanism by which they regulate sphingolipid production appear to be largely conserved throughout the fungal clade [40], the response we have described here likely plays an important role in the tolerance to acetic acid of many other yeast species, such as Z. bailii [52]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some attempts had been made to change sphingolipid content via engineering or the simulation of molecular dynamics (23-25). An increase in sphingolipids resulted in a Zygosaccharomyces bailii membrane, which was more packed and dense and increased acetic acid resistance (24). These findings indicated that the importance of developing novel strategies to improve stress resistance by engineering complex sphingolipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms underlying the response and extreme tolerance of Z. bailii to acetic acid are still poorly characterized, a number of relevant physiological strategies have been reported. These include the capacity of the yeast cells to tolerate short-term intracellular pH changes [11, 12], co-consume acetic acid and glucose [13–15] and exhibit high basal level of complex sphingolipids proposed to decrease plasma membrane permeability to this weak acid [16]. Also, a recent genome-wide study identified the Z. bailii transcription factor ZbMsn4 [17], homologous to the S. cerevisiae stress-responsive transcriptional activators Msn4 and Msn2 [18], as an acetic acid tolerance determinant.…”
Section: Introductionmentioning
confidence: 99%